Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1039/c4cc09513h
|View full text |Cite
|
Sign up to set email alerts
|

Towards engineering of self-assembled nanostructures using non-ionic dendritic amphiphiles

Abstract: We have reported on the formation of different self-assembled nanostructures by subtle changes in the structure of non-ionic dendritic amphiphiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 38 publications
5
53
0
Order By: Relevance
“…The guest encapsulation experiments were carried out as reported in the literature . A detailed description of the procedure as well as the mode of calculation of the encapsulation capacity are provided in the Experimental Section/Supporting Information.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The guest encapsulation experiments were carried out as reported in the literature . A detailed description of the procedure as well as the mode of calculation of the encapsulation capacity are provided in the Experimental Section/Supporting Information.…”
Section: Resultssupporting
confidence: 70%
“…The transport capacity of different amphiphiles with identical mPEG and alkyl chains showed similar trends for the two different guest molecules, indicating a strong relation between transport capacity and structure of the hosting amphiphile. The transport capacity of Nile Red is found to be in line with our previous report on nonionic dendritic amphiphiles displaying unexpected parameters in micellar assemblies, while for Nimodipinie these systems were found to be better than our previous reported system . For amphiphiles 2 and 4 having a short C 11 alkyl chain, it was observed that increasing the length of the mPEG head group from M n 350 ( 2 ) to 1000 ( 4 ) leads to a considerably decreased transport capacity for either of the guest molecules.…”
Section: Resultsmentioning
confidence: 66%
“…( 27 ) were prepared pursuant to reported literature procedures. [39][40][41] LA-NHS , 1-Azidooctadecane ( 26 ), and compound LA-G1-OH ( 14 ) were synthesized according to published protocols. [42][43][44] Synthetic details for the preparation of the noncrosslinkable control molecule Alkyl-Glycine ( 5 ) can be found in Figure S1, pp.…”
Section: Methodsmentioning
confidence: 99%
“…Further, it is inferred from the results that PG [G2.0] based nanocarriers 12 and 13 are more efficient drug/dye transporters (exception: Nile red encapsulation by amphiphile 13 ) in comparison to their analogous PEGylated amphiphiles reported earlier by our group . In addition, amphiphile 13 is found to be a better solubilizer for Nile red and nimodipine than the dendritic amphiphiles involving PG [G2.0] and [G3.0] dendrons as head groups and lipophilic tail segments having two alkyl chains (C 12 and C 18 ) reported in literature …”
Section: Resultsmentioning
confidence: 75%